Exploring the Impact of e-WOM on Generation Z Purchase Intention: The Mediating Role of Brand Image and Perceived Quality - Natalia, Hizkia Desy; Aprillia, Ariesya (Pandawan Sejahtera Indonesia, 2025)
This study aims to identify the impact of electronic word of mouth (e-WOM) on the purchase intention of Generation Z, considering e-WOM quantity, quality, and valence, as well as brand image and perceived quality as mediators. With the rapid rise of online platforms, e-WOM has become a key factor influencing consumer decision-making, particularly among digitally native groups like Generation Z. A total of 260 respondents, who met the inclusion criteria, were selected, with the study population consisting of Generation Z individuals resid-ing in Bandung. The purposive sampling technique was applied to ensure that participants had relevant experience with e-WOM. Data were collected using a questionnaire distributed via Google Forms, employing a Likert scale to measure responses. The analysis was carried out using the Structural Equation Modeling (SEM) method based on SmartPLS 4.0 as the testing tool, which allowed for the examination of both direct and indirect effects of e-WOM on purchase intention. The results of this study indicate that e-WOM quantity, quality, and valence have a positive and significant influence on purchase intention. These relationships were found to be both direct and indirect, highlighting the importance of e-WOM in shaping consumer behavior. A limitation of this study is that the sample only includes Generation Z in Bandung, which means the findings may not fully represent Generation Z in other regions or countries. Future research could expand the sample to improve generalizability and explore additional mediators in the e-WOM to purchase intention relationship